Sistem Pembayaran Tunai Dan Non Tunai Pada PT. Kedamaian - Alfiana, Yeni; Veronica, Aries; Yanti, Dwi; Winarsih, Wiwin (Jurnal Media Akuntansi (Mediasi), 2024)
ABSTRAK   The purpose of this research is to determine the differences in payment systems implemented by PT. Peace before and after cash and non-cash payments are made to the profit and loss statement by analyzing financial ratios and seeing the differences. The analysis technique used is the Paired Simple T-Test. The results of this research show that the sig cash ratio value is 0.347 > 0.05, there is no difference in the cash ratio between the income statement before and after the non-cash payment system. The sig value of Debt to Total Asset Ratio is 0.245 > 0.05, there is no difference in Debt to Total Asset Ratio between the income statement before and after the non-cash payment system. The sig value of Debt to Equity Ratio is 0.188 > 0.05, there is no difference in the Debt to Equity Ratio between the income statement before and after the non-cash payment system. The Profit Margin sig value is 0.915 > 0.05, there is no difference in Profit Margin in the income statement before and after the non-cash payment system. This shows that there is no significant difference before and after the non-cash payment system on the profit and loss statement, although only part of several variables.   Keywords: Profit and loss report, cash and non-cash payment systems, financial ratios.   ABSTRAK   Tujuan dari penelitian ini adalah untuk mengetahui perbedaan sistem pembayaran yang diterapkan oleh PT. Kedamaian sebelum dan sesudah dilakukan secara tunai dan non tunai terhadap laporan laba rugi dengan cara menganalisis rasio keuangan dan dilihat perbedaannya. Teknik analisis yang dipakai ialah Uji Paired simple T-Test. Hasil penelitian ini menunjukan nilai sig cash ratio bernilai 0.347 > 0.05,  tidak ada perbedaan cash ratio antara laporan laba rugi sebelum dan sesudah sistem pembayaran non-tunai. Nilai sig Debt to Total Asset Ratio bernilai 0.245 > 0.05,  tidak ada perbedaan Debt to Total Asset Ratio antara laporan laba rugi sebelum dan sesudah sistem pembayaran non-tunai. nilai sig Debt to Equity Ratio bernilai 0.188 > 0.05, tidak ada perbedaan Debt to Equity Ratio antara laporan laba rugi sebelum dan sesudah sistem pembayaran non-tunai. Nilai sig Profit Margin bernilai 0.915 > 0.05, tidak adanya perbedaan Profit Margin pada laporan laba rugi sebelum dan sesudah sistem pembayaran non-tunai. Ini menunjukan bahwa perbedaan sebelum dan sesudah sistem pembayaran non-tunai terhadap laporan laba rugi, tidak ada perbedaan signifikan, walaupun hanya sebagian dari beberapa variabel.   Kata Kunci : Laporan laba rugi, sistem pembayaran tunai dan non-tunai,rasio keuangan.